Silica Release from Silane Cross-Linked Gelatin Based Hybrid Scaffold Affects Cell Proliferation - Balavigneswaran C.K.; Venkatesan R.; Karuppiah P.S.; Kumar G.; Paliwal P.; Krishnamurthy S.; Kadalmani B.; Mahto S.K.; Misra N. (My University, 2025)
Earlier, we had reported the synthesis and characterization of star-shaped poly(d,l-lactide)-b-gelatin (ss-pLG) to improve cell adhesion and proliferation, but the stability of ss-pLG scaffolds remained a persistent issue. Here we show an increase in the stability of ss-pLG using 3-glycidoxypropyl trimethoxysilane (GPTMS) as a covalent cross-linker (h-ss-pLG). The rate of cell proliferation within Hep-G2 cultured h-ss-pLG scaffolds increased until the third day, and afterward it drastically declined. Further, we identified the release of inorganic silica from GPTMS cross-linked h-ss-pLG, which may be associated with the decrease in the rate of HepG2 cell proliferation. However, the cross-linking did not affect red blood cells (RBCs) and they were completely hemocompatible. In addition, our in vivo experiments in female rats showed that the hybrid h-ss-pLG scaffolds were not degraded completely after 4 weeks, as they were covalently cross-linked with silane. These results suggest the significance of the cross-linker selection, which is one of the other key factors, and needs to be considered while designing scaffolds. Copyright © 2019 American Chemical Society.